Development of new rectangular rubber isolators for a tunnel-form structure subjected to seismic excitations. (August 2021) - Altalabani, Diyar; Hejazi, Farzad; Saifulnaz Bin Muhammad Rashid, Raizal; Nora Aznieta Abd Aziz, Farah
Abstract: Nowadays, tunnel-form building systems are frequently implemented in the construction of various buildings due to the quick construction process. The rubber base isolator is one of the most successful and practical techniques to enhance the performance of structures against lateral loads. Although the conventional isolators are available in circular and square shapes, the anisotropic isolation system has typically been designed by employing symmetrical shaped seismic isolators that are not suitable for tunnel-form structural systems due to the special shape and configuration of these types of buildings. Therefore, an attempt was launched in this study to develop new rectangular base isolators with one, two, and four lead and rubber cores that are applicable for framed buildings such as tunnel-form structures. Thereafter, the rubber cores are confined through wrapping with one layer of CFRP sheet and stainless steel tube to increase the equivalent damping ratio of the devices and to dissipate the imposed vibrations. The results revealed that confining the rubber cores with CFRP and steel layers was substantially effective in improving the energy dissipation capacity of the proposed rectangular rubber isolators. Finally, the proposed isolators are implemented into a 5-story tunnel-form building and Incremental Dynamic Analysis (IDA) was conducted on both fixed base and base-isolated structures using a suite of 10 pairs of earthquake records. Overall, it can be concluded that even under severe earthquake excitations, the tunnel-form building studied herein can practically satisfy the Immediate Occupancy (I.O) performance level by occupying the proposed rectangular isolators.